LEXICAL COHESION OF JOE BIDEN’S SPEECH IN PHILADELPHIA: A DISCOURSE ANALYSIS - Agustina Sihombing; Robby Satria (PROJECT (Professional Journal of English Education), 2024)
In discourse analysis, speech was defined as a form of communication involving the production and expression of spoken language. In this study, researchers used spoken language, namely speech. This study aims to discover the types of lexical cohesion in Joe Biden’s speech in Philadelphia. The researchers applied Brian Paltridge’s theory, which divides lexical cohesion into six types: antonymy, collocation, synonymy, repetition, meronymy, and hyponymy. The qualitative method was used to carry out this study. The data collection method is observation with a note-taking technique by watching and listening to the data source. The analyzing data method is identification with an identity technique by classifying the data that have been collected. Results of this study, the researchers found 20 data related to the forms of lexical cohesion. There are 7 data containing antonymy, 1 data containing collocation, 3 data containing synonymy, and 9 data containing repetition. Repetition is a strategy of lexical cohesion that Joe Biden employed frequently to emphasize his points in each line of his statements. The researchers did not find the data related to meronymy and hyponymy, because there were no data related to part of a whole or no data showing a relationship between general and specific.